An Integrated Approach for Compendium Generator using Customized Algorithms - M. Suman; Tharun Maddu; M. Mohan (Institute of Advanced Engineering and Science, 2015)
Text Summarization is a process that is to give the shorter version of a text document. For many research scholars who want to do their research on a specific domain has to search a lot of documents on that topic related to a specific domain. It is also difficult to go through the lot of the research papers present in that particular domain which takes a lot of time at this moment of time there are lots of chances in missing some key words present in those research papers. So that Summarizer is used to give the summary of a paper. The aim of our project is to reduce the body of the text and maintaining coherence and avoiding redundancy. Winnowing is an algorithm that gives the coherence between the multiple papers when multiple papers are given as the input. Redundancy that is the repeated words or sentences can be avoided using the MMR algorithm.